2023
DOI: 10.3389/fphar.2023.1200054
|View full text |Cite
|
Sign up to set email alerts
|

Based on cuproptosis-related lncRNAs, a novel prognostic signature for colon adenocarcinoma prognosis, immunotherapy, and chemotherapy response

Abstract: Introduction: Colon adenocarcinoma (COAD) is a special pathological subtype of colorectal cancer (CRC) with highly heterogeneous solid tumors with poor prognosis, and novel biomarkers are urgently required to guide its prognosis.Material and methods: RNA-Seq data of COAD were downloaded through The Cancer Genome Atlas (TCGA) database to determine cuproptosis-related lncRNAs (CRLs) using weighted gene co-expression network analysis (WGCNA). The scores of the pathways were calculated by single-sample gene set en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…However, Liu and Zhang et al noted contrasting ndings and reported that CASC9 silencing suppressed colon cancer cell proliferation and invasion [33,34]. The risk signature for cuproptosis in colon cancer patients includes ZEB1-AS1 and SNHG7 [35,36], while ATP2A1-AS1 was incorporated into the lncRNA-based prognosis prediction model for cuproptosis in patients with cervical cancer [37]. SNHG7 has also been implicated in developing drug resistance in COAD [38], such as promoting anlotinib resistance in colon cancer [39].…”
Section: Discussionmentioning
confidence: 99%
“…However, Liu and Zhang et al noted contrasting ndings and reported that CASC9 silencing suppressed colon cancer cell proliferation and invasion [33,34]. The risk signature for cuproptosis in colon cancer patients includes ZEB1-AS1 and SNHG7 [35,36], while ATP2A1-AS1 was incorporated into the lncRNA-based prognosis prediction model for cuproptosis in patients with cervical cancer [37]. SNHG7 has also been implicated in developing drug resistance in COAD [38], such as promoting anlotinib resistance in colon cancer [39].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that lncRNAs may play a role in drug resistance in cancer. In the GEO database, Li et al 32 analyzed the GSE39582 CRC dataset and discovered 31downregulated lncRNAs and 16 upregulated lncRNAs. In 5-FU-resistant CRC cells, down-regulation of lncRNA snaR expression increases 5-FU sensitivity, overexpression of lncRNA CCAT1 (Colon cancer-associated transcript 1) reduced 5-FU sensitivity and apoptosis.…”
Section: Lncrna In Tumorigenesis and Chemotherapy Resistancementioning
confidence: 99%